2022
DOI: 10.1039/d2fo02303b
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus plantarumHNU082 alleviates dextran sulfate sodium-induced ulcerative colitis in mice through regulating gut microbiome

Abstract: Probiotic Lp082 treats ulcerative colitis by optimizing the gut microbiota and the intestinal mucosal barrier (biological, chemical, mechanical and immune barriers), regulating inflammatory and disease pathways and reducing neutrophil infiltration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 57 publications
4
17
0
Order By: Relevance
“…A deep Shotgun metagenomic sequence was used to perform microbial community diversity analysis. 40 HumanN2 metagenomic metabolic pathway annotations were constructed based on the UniRef90 database. 41 The R software and GraphPad software were used for statistical analysis.…”
Section: Rna Extraction Pcr Amplification Electrophoresis and 16s Rrn...mentioning
confidence: 99%
“…A deep Shotgun metagenomic sequence was used to perform microbial community diversity analysis. 40 HumanN2 metagenomic metabolic pathway annotations were constructed based on the UniRef90 database. 41 The R software and GraphPad software were used for statistical analysis.…”
Section: Rna Extraction Pcr Amplification Electrophoresis and 16s Rrn...mentioning
confidence: 99%
“…The relieving effect of L. plantarum on intestinal inflammation has been reported in other studies [ 56 , 57 ]. The gene expression and production of anti-inflammatory factors (IL-10, TGF-β1, and TGF-β2) increased in Caco-2 cells and a DSS-induced mouse model [ 58 , 59 ]. L. plantarum reduced the gene expression and production of pro-inflammatory cytokines (IL-1β, IL-6, TNF-α, MPO, and IFN-γ) and suppressed inflammatory responses to normalize the immune barrier [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that DSS-induced colitis caused a significant decrease in serum Trp content and increase in Kyn content, which was consistent with previous studies ( 32 34 ). The decrease in serum Trp content may be due to reduced food intake (the main source of Trp) in colitis mice ( 35 ). The elevation of Kyn content was mainly attributed to the decrease of its consumption.…”
Section: Discussionmentioning
confidence: 99%